Anthropometric Characteristics and Somatotype of Young Slovenian Tennis Players - Ales Germic; Tjasa Filipcic; Ales Filipcic (Applied Sciences)
Tennis is a demanding sport that requires physical abilities and optimal body composition. The aim of this study was to investigate the anthropometric characteristics, body composition, and somatotype development of young Slovenian tennis players (754 boys and 514 girls aged 12 to 18 years) over the last two decades. Using standardised anthropometric measurements and the Heath-Carter method, somatotypes were calculated and analysed by age and gender. The results showed clear age- and gender-specific trends and differences in both somatotype profiles and detailed anthropometric characteristics. Significant differences were found in height, body mass, BMI, skinfolds, girths, and limb lengths, with gender differences becoming more pronounced in the older age groups. In boys, mesomorphy increased with age, reflecting an increase in musculature, while in girls, a shift from ectomorphic to endomorphic profiles was observed during adolescence, probably influenced by pubertal and hormonal changes. Significant sex-specific differences were observed in all three somatotype components in most age groups, especially in fat mass and muscle. The longitudinal design provides valuable data and insights into the evolving physical profiles of adolescent tennis players that support more effective talent identification and training. Despite the changes that have taken place in tennis over time, standardised measurement protocols ensured comparability, making the results relevant for practitioners working with adolescents in tennis development.